Digital Book Hindu-Buddhist Kingdom in Palembang Based on Flipbook Maker for High School Students - Dominikus Doni Petun; Saefur Rochmat; Zulkarnain Zulkarnain (STAI Hubbulwathan Duri, 2023)
Teaching materials are learning tools that are used with the help of tools that facilitate the delivery of material during the learning process at school. A platform called Flipbook Maker provides open-access e-learning in the form of digital books. The purpose of this research is to evaluate the feasibility and effectiveness of Flipbook Maker-based learning media for e-learning. For class X SMA students, teaching materials were made in the form of digital books about the Kingdom of Sriwijaya with case studies at a junior high school in Sorong Regency. Development research with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation, is the research method used. Material experts, media experts, and linguists assigned “fit” scores to the research team's product during development. During the implementation phase, the researcher conducted tests with class X students of the school. Students in the Try Out One-to-One and Small Group Try Out groups evaluated the results of this implementation phase using the